Concentration Levels and Ecological Risks of Persistent Organic Pollutants in the Surface Sediments of Tianjin Coastal Area, China. (16th January 2013) - Lu, Xiaoxia; Chen, Chaoqi; Zhang, Shu; Hou, Zhen; Yang, Junjun
Abstract : Sediments were sampled from different surface water bodies in Tianjin coastal area, China, and persistent organic pollutants (POPs) including polycyclic aromatic hydrocarbons (PAHs), organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs) were measured using GC/MS or GC/ECD. The purposes were to investigate the concentration levels of the POPs and to assess their ecological risks. The results showed that all the 16 priority PAHs were detected from the 10 sediments sampled with the total concentrations of the 16 PAHs ranging from 274.06 μ g/kg to 2656.65 μ g/kg, while the concentrations of the halogenated POPs were generally low except in the Dagu waste discharging river where the total concentrations of 24 OCPs, 35 PCBs, and 14 PBDEs were 3103.36 μ g/kg, 87.31 μ g/kg, and 13.88 μ g/kg, respectively. In the studied sediments, PAHs exhibited risks to benthonic organisms; particularly the concentrations of naphthalene and/or acenaphthene exceeded their probable effect concentrations in several locations. In comparison, only in the Dagu waste discharging river, OCPs exhibited risks with the concentrations of heptachlor epoxide and lindane exceeding their probable effect concentrations. PCBs and PBDEs posed rare risks in the studied area.